2014
DOI: 10.2116/analsci.30.569
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Highly Sensitive Detection by a Real-time Polymerase Chain Reaction Using a Chip Coated with Its Reagents

Abstract: On-site detection by flow-through polymerase chain reaction (PCR) microfluidic systems for rapid and highly sensitive analysis, are significantly desired for bioanalytical and medical research. The conventional continuous-flow PCR chips realized rapid detection, but their sensitivity was very low (10 6 to 10 8 copies μL). We improved this drawback by coating the chip with a PCR reagents mixture, and succeed to obtain a rapid and highly sensitive detection by using a segment-flow PCR system. In the present work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, depending on the type of sample, adjustments during sample preparation may be required. Furutani et al ( 2014 ) reduced the run time to 8 min for the detection of E. coli with a high sensitivity of 4 cells μL −1 using a microfluidic RT-PCR chip coated with PCR reagents. The multiplexed detection of waterborne pathogens on a microfluidic RT-PCR chip has already been achieved (Ramalingam et al 2010 ).…”
Section: Future Trendsmentioning
confidence: 99%
“…However, depending on the type of sample, adjustments during sample preparation may be required. Furutani et al ( 2014 ) reduced the run time to 8 min for the detection of E. coli with a high sensitivity of 4 cells μL −1 using a microfluidic RT-PCR chip coated with PCR reagents. The multiplexed detection of waterborne pathogens on a microfluidic RT-PCR chip has already been achieved (Ramalingam et al 2010 ).…”
Section: Future Trendsmentioning
confidence: 99%
“…Rapid PCR conditions were optimized by adding a fluorescent dye to the PCR reagent in GeneSoC. In our previous studies, SpeedSTAR DNA HS Polymerase was used as the optimal enzyme for rapid fluorescence-based PCR amplification using the TaqMan probe method [ 15 , 17 , 18 ]. In the present study, we additionally confirmed rapid PCR amplification using KOD One polymerase, which lacks 5′ nuclease activity.…”
Section: Resultsmentioning
confidence: 99%
“…Use of TaqMan® probe DNA is a powerful tool for analyzing sequences of PCR products. However, real-time PCR systems using the TaqMan® probe can be affected by sample impurities, and the inhibitory activity of impurities against DNA polymerase depends on the type of DNA polymerase [44][45][46][47][48]. This observation suggests that suitable DNA polymerases may not always be used in real-time PCR because the system requires DNA polymerases that exhibit exonuclease activity.…”
Section: Comparison With Real-time Pcr Technologymentioning
confidence: 99%